Effectiveness of taping for Gluteal Muscle on gait velocity in Hemiparesis: Case series - DARSHNI.R.THAKKAR,; D. MALARVIZHI,; PEROORU RUPESH, (International Journal of Pharma and Bio Sciences, 2018)
The aim of the study was to find the effectiveness of taping for gluteal muscle on gait velocity in hemiparesis patients. The study design was Experimental Study. 5 patients of Hemiparesis with Inclusion criteria of gait abnormality with age group of 30-85 years of both genders with affected lower limb muscle power more than 2 will be included in the study. Exclusion criteria includes any patients with cardiac problems, any other neurological problems, visual and hearing deficit, Hip flexor and plantar flexor contractures, allergy to adhesive tape, non-co-operative patients .Gluteal taping was applied to 5 patients along with conventional therapy for 1 week. The gait velocity was measured before and after the intervention using 10 Meter Walk test. This study concluded that there was effectiveness of long term gluteal taping on gait velocity in hemiparesis patient.